PHENOTYPIC DETECTION AND ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF EXTENDED-SPECTRUM BETA LACTAMASE PRODUCING GRAM-NEGATIVE BACILLI - Dr. Arun Kumar Poyyamozhi , Dr. Poongodi Santhana kumarasamy , Dr. Velvizhi Gomathinayagam, Dr. Indira Ananthapadmanabasamy, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Globally, antimicrobialresistance emerges as one of the major public health threats. Excessive orinappropriate use of antimicrobials inhealthcare settings over the last fewdecades has been acontributing factor inthe emergence of drug resistance